Implementation Analysis of Integrated MSMEs Financial Statement System (SILARUM) - Hartati, Noorina; Kusuma Wardini, Amalia; Idrus, Olivia; Margunani, Margunani; Suci Rachmadani, Wulan; Asari, Ayu (European Journal of Applied Sciences, 2021)
Micro, Small, and Medium Enterprises (MSMEs) are vital to support the economy in Indonesia. The flow of globalization and high competition has caused MSMEs to face global challenges, such as improving product innovation, developing human resources and technology, expanding the marketing area, and applying professional management. The accounting recording system for MSMEs is found to ignore financial accounting standards. Factually, accurate and standardized financial reports will support MSME players in developing their business. This study aims to design an integrated financial application as a solution for MSMEs and assist them in applying financial accounting standards called SILARUM. Applying this system, hopefully, MSMEs can make accountable and transparent financial management systems for their business.